Embodied ecology: The eco-somatics of permaculture. Issue 1 (1st April 2018) - Nelson, Matthew
Embodied ecology is a functional philosophy, a model for how we participate in the choreography of our own experience. Applying ethics and principles to the material nature of the human endeavour, embodied ecology utilizes scientific information and methodology in distinctly subjective, artful ways. In this article I explore the confluence of themes emerging from the practical discipline of permaculture as described by David Holmgren and my own practice of somatics. This didactic scholarship is guided by a unifying ecological world-view: we are living systems.